HAK KEPEMILIKAN RUMAH TEMPAT TINGGAL ATAU HUNIAN OLEH ORANG ASING YANG BERKEDUDUKAN DI INDONESIA - Ni Made Sumerti Asih; Gusti Ayu Kade Komalasari (Universitas Mahendradatta, 2022)
For Indonesians and Indonesian legal entities, various land rights can be granted such as Hak Milik, Hak Guna Bangunan, Hak Guna Usaha, and Hak Guna Usaha, but for foreigners and foreign legal entities can only be granted Hak Use. Indonesian legal entities may be granted property rights for certain legal entities, such as socio-religious legal entities, foundations, cooperatives. The problem studied is that foreigners who are domiciled in Indonesia have the right to own a residential or residential house in Indonesia and the legal consequences if there is a violation of the ownership of a residential or residential house by a foreigner domiciled in Indonesia. According to Law Number 1 of 2011 concerning Housing and residential areas, Article 52 paragraph (1) states that foreigners can inhabit or occupy houses by means of Lease Rights or Use Rights. For a place to live, foreigners can rent houses owned by Indonesians or if they want to build their own houses, it is possible to control and use the land in question with Lease Rights or Use Rights. If the land in question is Indonesian-owned land, it can be with rental rights for buildings or use rights (Article 41 and 44 of the UUPA) and the legal consequences of violating the ownership of residential or residential houses by foreigners domiciled in Indonesia are legal consequences in the form of birth , change, or disappearance of a certain legal relationship and legal consequences in the form of sanctions, which are not desired by the legal subject. The legal consequence in the form of birth, change, or disappearance of a certain legal relationship is that since the right is requested either directly with the deed of release and deed of transfer of rights, then a new legal relationship is born, namely the transfer of rights or since the foreigner signs the deed of release and deed of transfer of rights. then at that time the party who gets the right or a foreigner becomes the legal owner